IN TEACHING THE SUBJECT OF PHYSICAL PROPERTIES OF SOUND THE IMPORTANCE OF TECHNICAL CAPITALITY - Irgashev Suyundik Uktamovich; Ahmadjonova Saltanat Zafar qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This in the article Medicine higher education in organizations Medical and biological physics education quality and efficiency increase for electron development (manuals) development that it was made and from him Foy dalanik Acoustics. Physical properties of sound to learn property and features and transversely and The determination of the speed of propagation of longitudinal waves is described and their study in the process apply experience test results given.